Exploring online mentoring with preservice teachers in a pandemic and the need to deliver quality education - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2021)
Purpose Social constructivism in teacher education highlights the importance of social interaction between preservice teachers (PTs) and their cooperating teachers (mentors) for effective mentoring. Mentoring relationship between PTs and mentors had to take a different path due to the pandemic when face-to-face education shifted to online education. The purpose of the present study was to explore online mentoring experience from the perspectives of PTs. Design/methodology/approach The methodology was qualitative. 35 randomly selected PTs were interviewed after the completion of an eight-week online school experience course. Data obtained from focus group interviews were analyzed using pattern coding. Findings Overall, the PTs mostly had a positive online mentoring experience. They reported receiving sufficient contextual and technological support when needed with limited professional support. However, they expected their mentors to allocate more time and their university supervisors (USs) to control practicum schools and to provide more online teaching samples and guidelines. They indicated that when they did not receive supports this was entirely due to the pandemic. Research limitations/implications This research could inform USs and mentors who coordinate mentoring programs at schools and universities so that they might take an urgent step to restructure mentorship training, putting emphasis on the online aspect. Given the number of the participants, this research is limited in scope. Originality/value This research contributes to a body of research that investigates how online mentoring may be more effective. To create positive online mentoring relationships, following suggestions are provided to mentors: providing ongoing online support to PTs to overcome online mentoring challenges, spending an extra hour with PTs for reflection and making use of multiple contexts for PTs' professional ownership.
Keywords: Mentoring; Online education; English language teacher education; Pandemic; Pre-service teachers